Fabricating Superhydrophobic Protective Films with Enhanced Self‐Cleaning and Anti‐Corrosion Properties through Multiple Anodic Oxidations on Aluminum Alloys. Issue 10 (9th March 2023) - Liu, Enhong; Zhou, Yuqin; Zhao, Shuang; Hao, Jiashuo; Hu, Yang; Su, Yuyu; Han, Jianhua
Abstract: The development of aluminum (Al) alloys with superb anti‐corrosion and self‐cleaning properties for prolonging the working life and reducing maintenance cost is a hot topic of concern. Since anodic oxidation has been proven to be an effective technique to prepare micro or nanostructures on Al alloys surface, this study proposes a novel and scalable multiple anodic oxidations method with gradient current densities for fabricating hierarchical micro‐nanostructure film with appropriate roughness on Al alloys, while the SiO2 ‐silane film reduced the surface free energy and enhanced the surface chemical inert state. As expected, the surface of Al alloys modified with the multiple anodic oxidations and SiO2 ‐silane film has the most substantial hydrophobic properties, with contact angle up to 166°, rolling angle as low as 3.17° and excellent non‐sticking effect of water droplets. This method enables the Al alloys surface to have excellent self‐cleaning performance and corrosion resistance with protection efficiency up to 98.81 %. This multiple anodic oxidations method has a wide range of references for the modulation of micro‐nanostructure on Al alloys surface and other metallic substrates to assemble superhydrophobic protective films. Abstract : The surface of Al alloys modified with multiple anodic oxidations and SiO2 ‐silane film has the strongest hydrophobic properties, with contact angle up to 166°, rolling angle as low as 3.17° and excellent non‐sticking effect of water droplets. This method enables the Al alloys surface to have excellent self‐cleaning and corrosion resistance with protection efficiency up to 98.81 %.